Crowned Dens Syndrome: A Rare Cause of Sudden Onset Neck Pain - Butt, Nauman Ismat; Rasheed, Muhammad Bilal; Ashfaq, Fahmina; Anser, Aniqa (International Journal of Integrated Health Sciences, 2023)
Objective: To report a case of Crowned Dens Syndrome (CDS), which is a rare disorder caused by crystal deposition by calcium pyrophosphate dihydrate in the peridontoid soft tissues surrounding the C1 and C2 vertebrae that presents in elderly with sudden onset neck pain, neck stiffness, fever, and elevated inflammatory markers, with periodontal calcification in a halo or crown configuration on radiography considered diagnostic.Methods: A 64-year-old diabetic and hypertensive female patient presented with a 6-day history of sudden onset posterior neck pain and stiffness. Movements of the cervical spine were equally limited in all directions, causing marked aggravation of pain. There was no focal neurologic loss. Her inflammatory markers were markedly raised.Results: Based on radiography, she was diagnosed with Crowned Dens syndrome and started on oral prednisolone, paracetamol, and tizanidine along with topical diclofenac. Oral NSAIDs were contraindicated due to her renal insufficiency.Conclusion: Crowned Dens Syndrome (CDS) is a rare cause of neck pain. Clinicians should consider this syndrome in their differential diagnosis. Timely diagnosis and treatment of CDS will lead to avoidance of unnecessary investigations and medications in such patients, along with a reduction in the length of stay.